Design and development of shovel type-spring steel furrow opener for cultivator mounted seed metering mechanism - Verma, Ajay; Shrivastava, Ankitesh (BIBECHANA, 2017)
The cultivator mounted seed metering mechanism consists of cultivator frame, tines, seed box, seed tubes, metering mechanism, power transmission unit, furrow opener and hitching attachments. The drawings of the developed machine were generated using CAD software and the machine was fabricated in the workshop of Faculty of Agricultural Engineering, IGAU, Raipur. Power was transmitted from ground wheel through sprocket-chain drive to the main shaft. At the average working speed of 3.8 km/h of tractor drawn cultivator, depth of operation was found 129 mm, average weed efficiency was found 76.42 %,effective field capacity was found 0.826 ha/h with field efficiency of 87.40 %. The cost of operation and energy requirement of cultivator was found to be Rs 387 per ha and 241 MJ/ha. The Energy requirement for cultivator-cum-seed drill was found to be 454.18 MJ/ha. BIBECHANA 15 (2018) 79-84